Event loading drives distribution of the organochlorine pesticide metabolite DDE in a sub-tropical river system, Brisbane River, Australia. (September 2021) - Grinham, Alistair; Deering, Nathaniel; Beecroft, Ryan; Rudd, Jessica; Heatherington, Craig; Cossu, Remo; Linde, Michael; Richardson, Darren; Wilson, Craig; Hutley, Nicholas; Albert, Simon
Abstract: Past catchment practices can contribute to environmental impacts for decades following their cessation. We examine the distribution of the prevalent organochlorine pesticide, dichlorodiphenyltrichloroethane (DDT) and its metabolites (DDE, DDD) in the sediments of a sub-tropical river system (Brisbane River, Australia). This study aimed to identify sources of DDT, DDE, DDD into the lower reaches of the Brisbane River. Annual sediment sampling of the lower Brisbane River over a period of 15 years (2001–2015) revealed a significant increase in sediment DDT, DDE and DDD content following major floods. A regional survey detected elevated sediment DDT, DDE and DDD content at 32 of 79 sites sampled; however, these were generally below guideline trigger values. DDE was the sole fraction at all but one site with creek systems dominated by intensive cropping practices identified as legacy sources and major flood events as a driver of elevated sediment DDE content in the lower reaches. Highlights: Upper reach catchments with intensive horticultural cropping were identified as a source of legacy DDT, DDE and DDD 32 of 79 sites in a regional survey had detectable DDT, DDE and DDD content with DDE the sole fraction in 98% of detections Pathway identified that transports DDT, DDE and DDD from horticultural cropping area to creek bed Floods increased sediment DDT, DDE and DDD content in lower reaches